2013
DOI: 10.1002/cmdc.201300032
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of Quinoxaline‐Based 5‐HT3A and 5‐HT3AB Receptor‐Selective Ligands

Abstract: Until recently, discriminating between homomeric 5-HT3A and heteromeric 5-HT3AB receptors was only possible with ligands that bind in the receptor pore. This study describes the first series of ligands that can discriminate between these receptor types at the level of the orthosteric binding site. During a recent fragment screen, 2-chloro-3-(4-methylpiperazin-1-yl)quinoxaline (VUF10166) was identified as a ligand that displays an 83-fold difference in [3H]granisetron binding affinity between 5-HT3A and 5-HT3AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Comparable levels of potency have been reported elsewhere when using a fragment-based approach, including targets as diverse as β2-adrinergic receptors, histamine receptors, protein kinase C, cAMP-specific 3′,5'-cyclic phosphodiesterase 4D and acetylcholine binding protein, β-secretase and BACE-1 ( Murray et al., 2007 , Wang et al., 2010 , Scott et al., 2012 , de Graaf et al., 2013 ). Importantly, when we have used a similar fluorometric approach on other ligand-gated ion channels we also identified novel fragments, showing the general applicability of the approach ( Thompson et al., 2012 , Verheij et al., 2012 , Thompson et al., 2013 ).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Comparable levels of potency have been reported elsewhere when using a fragment-based approach, including targets as diverse as β2-adrinergic receptors, histamine receptors, protein kinase C, cAMP-specific 3′,5'-cyclic phosphodiesterase 4D and acetylcholine binding protein, β-secretase and BACE-1 ( Murray et al., 2007 , Wang et al., 2010 , Scott et al., 2012 , de Graaf et al., 2013 ). Importantly, when we have used a similar fluorometric approach on other ligand-gated ion channels we also identified novel fragments, showing the general applicability of the approach ( Thompson et al., 2012 , Verheij et al., 2012 , Thompson et al., 2013 ).…”
Section: Resultsmentioning
confidence: 75%
“…Using FBDD, 1 /diverse chemical space can be efficiently described by smaller numbers of lower molecular weight and lower complexity compounds, 2 /lower complexity raises the chance of identifying protein-ligand interactions ( Hann et al., 2001 ), 3 /small fragment libraries (∼1000 compounds) typically result in a higher hit rate than when screening drug-like compounds ( Schuffenhauser et al., 2005 , Albert et al., 2007 , Siegal et al., 2007 , Chen and Hubbard, 2009 , Gupta et al., 2009 ), 4 /hit fragments are easier to optimize to improve their affinities and drug-like properties, and 5 /FBDD is design-intensive rather than resource-intensive ( Rees et al., 2004 ). Using this method we have had previous success in identifying novel drugs for other ligand-gated ion channel targets ( Thompson et al., 2012 , Verheij et al., 2012 , Thompson et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…24b in order to highlight their similarities and buttress the binding behavioural pattern demonstrated in Fig. 24a [205].…”
Section: Molecular Modelling and Binding Studymentioning
confidence: 97%
“…Studies of the 5-HT 3 A receptor have identified an aromatic binding cavity formed by residues Trp90 (loop D), Trp183 (loop B) and Tyr234 (loop C), mutagenesis of which effects both 5-HT activation and the binding of 5-HT 3 receptorcompetitive antagonists (Fig. 24a) [205]. The composite binding pocket allowed a clear identification of features which could be successfully engaged in the design of new inhibitors as well as potential drugs [205].…”
Section: Molecular Modelling and Binding Studymentioning
confidence: 98%
See 1 more Smart Citation